LAND LAW IN THE COMMUNAL RIGHTS OF THE COMMUNITY - Hamler Hamler; Leonard C. Opara (PENA LAW: International Journal of Law, 2022)
Land has an important role to human livelihood and the economic need for land that is inversely proportional to the availability of the amount of land (tendrung is static) to be one factor triggering the spike in the number of disputes, conflicts and land affairs that occurred in Indonesia. Land use change can be a cause of disputes followed by the development of plantation development that continues to increase causing increased demand for land. Communal rights to customary community land should be given legal protection. These communal rights shall be regulated in the Regulation of the Minister of Agrarian Affairs / Spatial Planning and Head of BPN Number 10 of 2016, and in particular the provisions of Article 16 paragraph 1 h jo Section 53 of the BAL, In case of land rights disputes granted to legal subjects with communal rights of customary law community then the law must be enforced in its settlement to be resolved through the Court (litigation) of the institution having the authority to resolve the dispute and settlement of a non litigation dispute or alternative disputes resolution. Alternative dispute resolution in the form of win-win solusen that can provide mutual benefit.